Use of paracetamol in sows around farrowing: effect on health and condition of the sow, piglet mortality, piglet weight and piglet weight gain - Kuller, Wikke; Sietsma, Steven; Hendriksen, Susan; Sperling, Daniel (Porcine health management, 2021)
BACKGROUND: Pain and fever in the periparturient period can lead to prolonged farrowing and can slow down the recovery of the sow, which will have an effect on the vitality and survival of the piglets. This study investigated the use of orally administered Paracetamol (Pracetam- CEVA) in sows in the periparturient period. RESULTS: Mortality did not differ in piglets during the first week, or during total lactation (P > 0.10). No difference was found in weight or weight gain of the piglets during lactation. The coefficient of variation of piglet weight was smaller in the Paracetamol (Pm) group at day 7, day 14 and at weaning, but not at birth. So, the variation within litters was smaller in the Pm- treated sows, in comparison with the Control (C) litters. No difference in mean IgG concentration was found between treatments, but the coefficient of variation was too high (> 40) in 50% of the C litters and not in Pm litters. The Pm- treated sows lost less backfat than the C- sows. No effect was found on the body temperature of the sows, but fever was rare in both groups. CONCLUSION: Paracetamol results in less variation of body weight of piglets during lactation, seems to have a potential effect on the distribution of IgG within litters and has a positive effect on backfat loss. The effects of Paracetamol might be even more pronounced in farms with high piglet mortality (this farm only 8%) or with a high incidence of agalactia, fever after farrowing or piglet diarrhoea, which was not the case in this farm. Paracetamol is a promising product for increasing the welfare in lactating sows and optimising production in the farrowing stable.
Keywords: Welfare; Immunocrit; Farrowing; Piglet; Paracetamol; Sow; Weight gain